Efficacy of omalizumab (Xolair®) in patients with moderate to severe predominately chronic oral steroid dependent asthma in Taiwan: a retrospective, population-based database cohort study. Issue 1 (December 2016) - Chen, Hao-Cheng; Huang, Chien-Da; Chang, Erin; Kuo, Han-Pin
Abstract Background Omalizumab (Xolair®), a recombinant monoclonal anti-IgE antibody, has demonstrated efficacy in clinical trials conducted in patients with moderate to severe persistent allergic asthma. We aimed to investigate the efficacy, discontinuation and medical resource utilization of omalizumab in the real-life setting in Taiwan. Methods This study was a retrospective, population-based database cohort study using the Taiwan NHIRD from 2007 to 2011 assessing the efficacy of omalizumab therapy over 4 months on changes in asthma medication, asthma control, frequency of exacerbations and hospitalization rates at baseline and after omalizumab discontinuation. Results There was a reduction in asthma medication post omalizumab therapy and severe exacerbations and hospitalizations from baseline (31.2 %, n  = 282) to the end of follow-up (11.8 %, n  = 144, p  < 0.001). Nearly all the patients received chronic oral corticosteroids at baseline (92.4 %). The number of ER visits decreased from 1.13 ± 2.04 to 0.29 ± 0.83, and the mean number of admissions decreased from 5.93 ± 16.16 to 2.75 ± 12.02 from baseline to the end of follow-up (p  < 0.001). After discontinuation of omalizumab, the cost of ER medical expenses decreased from New Taiwan dollars (NTD) 3934 at 2 months to NTD 2860 at 12 months. Conclusions Patients who received omalizumab therapy for over 4 months were more likely to reduce the use of other asthma medications and less likely to experience an asthma exacerbation, ER visits, and hospitalization, even after the discontinuation of omalizumab. These data suggest that omalizumab has efficacy in improving health outcomes in patients with moderate to severe predominately chronic oral steroid dependent asthma in the real-life setting in Taiwan.